Data Protection-Aware Design for Cloud Services. - Creese, S; Hopkins, P; Pearson, S; Shen, Y (Springer, 2009)
The Cloud is a relatively new concept and so it is unsurprising that the information assurance, data protection, network security and privacy concerns have yet to be fully addressed. This paper seeks to begin the process of designing data protection controls into clouds from the outset so as to avoid the costs associated with bolting on security as an afterthought. Our approach is firstly to consider cloud maturity from an enterprise level perspective, describing a novel capability maturity model. We use this model to explore privacy controls within an enterprise cloud deployment, and explore where there may be opportunities to design in data protection controls as exploitation of the Cloud matures. We demonstrate how we might enable such controls via the use of design patterns. Finally, we consider how Service Level Agreements (SLAs) might be used to ensure that third party suppliers act in support of such controls. © 2009 Springer-Verlag.